O-linked glycosylation in focus - Van den Steen, P; Rudd, P; Wormald, M; Dwek, R; Opdenakker, G (2000)
Important progress has been made recently in the development of analytical technology for O-linked oligosaccharide structure determination. Methods were developed for the chemical release (and subsequent labeling) of O-linked glycans from glycoproteins, e.g. by β-elimination or by hydrazinolysis. Different HPLC-methods and mass-spectrometry have become available as sensitive and sophisticated tools for the structural analysis of O-linked sugars. Site-specific glycan analysis is now technically achievable. Although functional analysis of O-linked glycans is still difficult, various roles have been established and some generalizations have emerged. O-linked glycans may play important roles maintaining the three-dimensional structure of the glycoprotein through intramolecular interactions, leading to the extension of the glycoprotein (O-linked). In some cases such domains function as molecular spacers and may fulfil the same role in membrane-bound receptors where the functional part of the receptor is oriented to the extracellular space because of the presence of glycans. Also O-linked sugars are essential in intermolecular interactions, e.g. in the recognition between glycoproteins. They can influence the activities of signaling molecules and enzymes, and are essential for cellular glycoprotein expression and processing. The alternative splicing of O-glycosylated Ser/Thr-rich domains confers an additional regulation level for the properties and activity of different glycoproteins. Additionally, involvement of alterations of O-linked glycosylation in health and disease is also relevant for further developments in human medicine.